Primary Ciliary Dyskinesia - Shoemark, Amelia; Harman, Katharine (Seminars in Respiratory and Critical Care Medicine, 2021)
Primary ciliary dyskinesia (PCD) is an inherited cause of bronchiectasis. The estimated PCD prevalence in children with bronchiectasis is up to 26% and in adults with bronchiectasis is 1 to 13%. Due to dysfunction of the multiple motile cilia of the respiratory tract patients suffer from poor mucociliary clearance. Clinical manifestations are heterogeneous; however, a typical patient presents with chronic productive cough and rhinosinusitis from early life. Other symptoms reflect the multiple roles of motile cilia in other organs and can include otitis media and hearing loss, infertility, situs inversus, complex congenital heart disease, and more rarely other syndromic features such as hydrocephalus and retinitis pigmentosa. Awareness, identification, and diagnosis of a patient with PCD are important for multidisciplinary care and genetic counseling. Diagnosis can be pursued through a multitest pathway which includes the measurement of nasal nitric oxide, sampling the nasal epithelium to assess ciliary function and structure, and genotyping. Diagnosis is confirmed by the identification of a hallmark ultrastructural defect or pathogenic mutations in one of > 45 PCD causing genes. When a diagnosis is established management is centered around improving mucociliary clearance through physiotherapy and treatment of infection with antibiotics. The first international randomized controlled trial in PCD has recently been conducted showing azithromycin is effective in reducing exacerbations. It is likely that evidence-based PCD-specific management guidelines and therapies will be developed in the near future. This article examines prevalence, clinical features, diagnosis, and management of PCD highlighting recent advances in basic science and clinical care.
Keywords: cilia; bronchictasis; diagnosis; management